Stimulation of the soluble guanylate cyclase (sGC) inhibits fibrosis by blocking non-canonical TGF? signalling - Beyer, Christian; Zenzmaier, Christoph; Palumbo-Zerr, Katrin; Mancuso, Rossella; Distler, Alfiya; Dees, Clara; Zerr, Pawel; Huang, Jingang; Maier, Christiane; Pachowsky, Milena; Friebe, Andreas; Sandner, Peter; et al. (Annals of the Rheumatic Diseases, 2015)
We have previously described the antifibrotic role of the soluble guanylate cyclase (sGC). The mode of action, however, remained elusive. In the present study, we describe a novel link between sGC signalling and transforming growth factor ? (TGF?) signalling that mediates the antifibrotic effects of the sGC.Human fibroblasts and murine sGC knockout fibroblasts were treated with the sGC stimulator BAY 41-2272 or the stable cyclic guanosine monophosphate (cGMP) analogue 8-Bromo-cGMP and stimulated with TGF?. sGC knockout fibroblasts were isolated from sGCI(fl/fl) mice, and recombination was induced by Cre-adenovirus. In vivo, we studied the antifibrotic effects of BAY 41-2272 in mice overexpressing a constitutively active TGF-?1 receptor.sGC stimulation inhibited TGF?-dependent fibroblast activation and collagen release. sGC knockout fibroblasts confirmed that the sGC is essential for the antifibrotic effects of BAY 41-2272. Furthermore, 8-Bromo-cGMP reduced TGF?-dependent collagen release. While nuclear p-SMAD2 and 3 levels, SMAD reporter activity and transcription of classical TGF? target genes remained unchanged, sGC stimulation blocked the phosphorylation of ERK. In vivo, sGC stimulation inhibited TGF?-driven dermal fibrosis but did not change p-SMAD2 and 3 levels and TGF? target gene expression, confirming that non-canonical TGF? pathways mediate the antifibrotic sGC activity.We elucidated the antifibrotic mode of action of the sGC that increases cGMP levels, blocks non-canonical TGF? signalling and inhibits experimental fibrosis. Since sGC stimulators have shown excellent efficacy and tolerability in phase 3 clinical trials for pulmonary arterial hypertension, they may be further developed for the simultaneous treatment of fibrosis and vascular disease in systemic sclerosis.
EVALuna2:12978